Partially resistant Cucurbita pepo showed late onset of the Zucchini yellow mosaic virus infection due to rapid activation of defense mechanisms as compared to susceptible cultivar - Nováková, Slavomíra; Flores-Ramírez, Gabriela; Glasa, Miroslav; Danchenko, Maksym; Fiala, Roderik; Skultety, Ludovit (Frontiers in Plant Science, 2015)
Zucchini yellow mosaic virus (ZYMV) is an emerging viral pathogen in cucurbit-growing areas wordwide. Infection causes significant yield losses in several species of the family Cucurbitaceae. To identify proteins potentially involved with resistance towards infection by the severe ZYMV-H isolate, two Cucurbita pepo cultivars (Zelena susceptible and Jaguar partially resistant) were analyzed using a two-dimensional gel electrophoresis-based proteomic approach. Initial symptoms on leaves (clearing veins) developed 6-7 days post inoculation (dpi) in the susceptible C. pepo cv. Zelena. In contrast, similar symptoms appeared on the leaves of partially resistant C. pepo cv. Jaguar only after 15 dpi. This finding was confirmed by immune-blot analysis which showed higher levels of viral proteins at 6 dpi in the susceptible cultivar. Leaf proteome analyses revealed 28 and 31 spots differentially abundant between cultivars at 6 and 15 dpi, respectively. The variance early in infection can be attributed to a rapid activation of proteins involved with redox homeostasis in the partially resistant cultivar. Changes in the proteome of the susceptible cultivar are related to the cytoskeleton and photosynthesis.